Case report: Clearance of longstanding, immune-deficiency-associated, vaccine-derived polio virus infection following remdesivir therapy for chronic SARS-CoV-2 infection - Bermingham, William Hywel; Canning, Benjamin; Wilton, Thomas; Kidd, Michael; Klapsa, Dimitra; Majumdar, Manasi; Sooriyakumar, Kavitha; Martin, Javier; Huissoon, Aarnoud P. (Frontiers in Immunology, 2023)
The global polio eradication campaign has had remarkable success in reducing wild-type poliovirus infection, largely built upon the live attenuated Sabin oral poliovirus vaccine. Whilst rare, vaccine poliovirus strains may cause infection and subsequently revert to a neurovirulent type, termed vaccine-derived poliovirus (VDPV). Persistent, vaccine derived infection may occur in an immunocompromised host (iVDPV), where it is a recognised complication following receipt of the Sabin vaccine. This has significant implications for the global polio eradication campaign and there is currently no agreed global strategy to manage such patients.Here we describe a case of a 50-year-old man with common variable immune deficiency, persistently infected with a neurovirulent vaccine-derived type 2 poliovirus following vaccination in childhood. iVDPV infection had proven resistant to multiple prior attempts at treatment with human breast milk, ribavirin and oral administration of a normal human pooled immunoglobulin product. His iVDPV infection subsequently resolved after 12 days treatment with remdesivir, an adenosine analogue prodrug that is an inhibitor of viral RNA-dependent RNA polymerase, administered as treatment for a prolonged, moderate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. iVDPV from the patient, isolated prior to treatment, was subsequently demonstrated to be sensitive to remdesivir in vitro. Based on the observations made in this case, and the mechanistic rationale for use with iVDPV, there is strong justification for further clinical studies of remdesivir treatment as a potentially curative intervention in patients with iVDPV infection.